Differential Probability Discounting Rates of Gamblers in an American Indian Population - Schneider, Tadd D.; Gunville, Jordyn A.; Papa, Vlad B.; Brucks, Morgan G.; Daley, Christine M.; Martin, Laura E.; Jarmolowicz, David P. (Frontiers in Behavioral Neuroscience, 2022)
Probability discounting, a subset of Behavioral Economic research, has a rich history of investigating choice behavior, especially as it pertains to risky decision making. Gambling involves both choice behavior and risky decision making which makes it an ideal behavior to investigate with discounting tasks. With proximity to a casino being one of the biggest risk factors, studies into the American Indian population have been a neglected population of study. Using outcome measures from a pre-scan probability discounting task, the current study equated the scan task to evaluate behavioral and neurobiological differences in gamblers versus non-gamblers. Gamblers showed differences in behavioral tasks (lower discounting rates) but not in patterns of neural activation.